PELATIHAN BANTUAN HIDUP DASAR (BASIC LIFE SUPPORT) BAGI MAHASISWA UNIVERSITAS PATTIMURA PADA PANDEMI COVID-19 - Ony Wibriyono Angkejaya; Beytriks Pattiasina; Marthen Matakupan; Annastasia Ohoiulun (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Cardiac arrest is a very important global health problem, in which a quick initial assessment and a correct and fast response can prevent death or disability. In 2018, the incidence of heart disease in Maliku based on doctors diagnosis was increased to 1.5%. A current incident of heart disease and a previous history of heart disease are both the biggest risk factors that could contribute to a sudden cardiac arrest in a person. So it is imperative for everybody, including students of Pattimura university from various faculties, not just healthcare providers, to know and understand how to perform Basic Life Support on any given situation. The result expected from this training is for the students of Pattimura University to be able to understand the theories and the techniques in assessing an emergency situation and performing BLS to those in need.